Melihat Perspektif Kinerja dengan Value for Money - Silfyana Cahya Manggar Mahdita; Ikhsan Budi Riharjo; Lilis Ardini (Jur. Akuntansi, Politeknik Negeri Malang, 2021)
The purpose of this study is to understand and identify the concept of performance appraisal using the value for money perspective. . Society often views public sector organizations as a hotbed of waste, a source of leakage of funds, and an institution that is always at a loss. The results of this study indicate that the UPTD Tugu Pahlawan, Balai Pemuda and THR have been running effectively, efficiently and economically. There are 3 (three) keys that are applied by this UPTD in maintaining the level of Value for Money in their activities, namely collaboration, evaluation and innovation. Good collaboration between parties in internal and external organizations will be able to increase effectiveness. Evaluation of performance will make employees improve and make new innovations to increase revenue and save expenses. By doing these three things, good corporate governance will be achieved.AbstrakTujuan penelitian ini guna memahami dan mengidentifikasi konsep penilaian kinerja isntansi yang menggunakan metode perspektif value for money. Metode ini dilakukan dengan pendekatan kualitatif dengan paradigma interpretatif. Hasil menunjukkan organisasi berjalan secara efektif, efisien dan ekonomis. 3 kunci yang diterapkan UPTD dalam menjaga tingkat Value for Money kegiatan mereka yaitu kerjasama, evaluasi dan inovasi. Kerjasama yang baik di internal eksternal organisasi akan meningkatkan efektifitas. Evaluasi kinerja membuat pegawai berbenah dan melakukan inovasi baru untuk meningkatkan pendapatan dan menghemat pengeluaran. Dengan melakukan hal tersebut akan diraih good corporate governance.